2006
DOI: 10.1093/cercor/bhl051
|View full text |Cite
|
Sign up to set email alerts
|

Altered Neocortical Cell Density and Layer Thickness in Serotonin Transporter Knockout Mice: A Quantitation Study

Abstract: The neurotransmitter serotonin (5-HT) plays morphogenetic roles during development, and their alteration could contribute to autism pathogenesis in humans. To further characterize 5-HT's contributions to neocortical development, we assessed the thickness and neuronal cell density of various cerebral cortical areas in serotonin transporter (5-HTT) knockout (ko) mice, characterized by elevated extracellular 5-HT levels. The thickness of layer IV is decreased in 5-HTT ko mice compared with wild-type (wt) mice. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 60 publications
1
59
0
Order By: Relevance
“…Indeed, the use of SSRI medications for the treatment of some facets of autism indicate that ongoing dysfunction in 5-HT networks may be an enduring facet of idiopathic autism and gives hope that further inspection of signalling deficits attributable to rare SERT variants can provide a meaningful advance in autism therapeutics. Rodent studies demonstrate a significant effect on brain structure (Persico et al 2003;Altamura et al 2007) and behaviour (Holmes et al 2002(Holmes et al , 2003 following genetic or pharmacological manipulations of SERTand/ or 5-HT during development (Whitaker-Azmitia et al 1996;Bengel et al 1998). In this regard, recent studies examining a common SERT promoter polymorphism (5HTTLPR) have linked autism-associated changes Autism-associated SERT coding variants H. C. Prasad et al 169 in brain size to altered SERT expression (Wassink et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the use of SSRI medications for the treatment of some facets of autism indicate that ongoing dysfunction in 5-HT networks may be an enduring facet of idiopathic autism and gives hope that further inspection of signalling deficits attributable to rare SERT variants can provide a meaningful advance in autism therapeutics. Rodent studies demonstrate a significant effect on brain structure (Persico et al 2003;Altamura et al 2007) and behaviour (Holmes et al 2002(Holmes et al , 2003 following genetic or pharmacological manipulations of SERTand/ or 5-HT during development (Whitaker-Azmitia et al 1996;Bengel et al 1998). In this regard, recent studies examining a common SERT promoter polymorphism (5HTTLPR) have linked autism-associated changes Autism-associated SERT coding variants H. C. Prasad et al 169 in brain size to altered SERT expression (Wassink et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…189,336 In addition, behavioral and neurological profiles for Sert-null mice can differ dependent on background strain. 188,191 The C57BL/6 mouse strain has been used as the background for many mutant lines, but studies in the fragile X-model mouse have suggested that this strain has less susceptibility to the effects of Fmrp deficiency. 51,61,65 C57BL/6J mice are also characterized by high-frequency hearing loss 337 and markedly low acquisition of a T-maze learning task, 17 indicating possible issues with using this strain as a background for mutant lines.…”
Section: Discussionmentioning
confidence: 99%
“…184,185 Similarly, mice with a targeted disruption of Sert also have an excess of 5-HT in the extracellular space, leading to disruption of somatosensory cortex formation, reduction of apoptosis in the telencephalon 186,187 and variable alterations in cortical layer thickness and neuronal cell density, dependent on background strain. 188 Sert-null mice also show an altered behavioral phenotype, including hypolocomotion, marked reductions in exploration, and reduced social interaction. 189,190 As with the altered parameters of brain growth, 188 observation of behavioral changes in Sertnull mice may be dependent on background strain.…”
Section: Autism Candidate Genes and Synaptic Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brains were subsequently sectioned and mounted in Flouromount G with DAPI (Southern Biotechnology). We imaged the DiO electrode tracks on a Zeiss Axio Imager 2 to confirm that penetrations were specific to monocular V1 (Antonini et al, 1999;Altamura et al, 2007;Niell and Stryker, 2008) and to determine the location of the electrode tips relative to the cortical layer.…”
Section: Methodsmentioning
confidence: 99%